Asian American art : (Stanford University Press, 2008)
This pioneering work recovers the extraordinarily impressive artistic production of numerous Asian Americans, and offers richly informed interpretations of a long-neglected art history. To unravel the complexity of Asian American art expression and its vital place in American art, the texts consider aesthetics, the social structures of art production and criticism, and national and international historical contexts. Without a doubt, Asian American Art will profoundly influence our understanding of the history of art in America and the Asian American experience for years to come.